Rancang Bangun Sistem Informasi Surat Perintah Perjalanan Dinas - Ester Laekha (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Abstract — This paper will propose information system design for SPPD application. Currently  Research Center for Physics LIPI still implement manual  way to issue SPPD. By observing manual way of issued SPPD and reference study of  normalization data method, a design of information system is proposed. It is found that third form of normalization is enough to organize data  inside database. Keywords—Data Normalisation , Information System, SPPD.